The dilemma between helping and perpetuating the problem: Kupang city's public perception of child beggars or vendors at traffic lights - Mite, Petrus Selestinus; Jehamat, Lasarus; Jeraman, Maria Roshanty Trinitasya Djoka; Tiran, Irma Susanti (The International Journal of Politics and Sociology Research, 2026)
This study looks at the moral conundrum that drivers in Kupang, Indonesia, face every day when they come across street merchants and child beggars at traffic signals. There is a conflict between the want to help out out of sympathy and the worry that doing so could make the child's precarious condition worse. The study explores how people understand and navigate these fleeting street interactions using a qualitative technique and Symbolic Interactionism as its theoretical framework. It concludes that visual clues, such as the children's looks, gestures, and approaches to cars, significantly influence public perception and reaction. Giving is primarily motivated by sympathy, but this inclination is crucially moderated by the knowledge that financial support may unintentionally prolong homelessness, interfere with education, and raise vulnerability to exploitation. As a result, people learn sophisticated, practical ways to deal with this dilemma. These include giving under certain conditions, providing food or beverages rather than money, or purposefully refusing material assistance while still being courteous and compassionate. The survey also shows that the public holds family and political institutions accountable for systemic solutions, with a focus on protection, support, and regulation. The study advances theory by showing how Symbolic Interactionism clarifies a contemporary urban conundrum, emphasizing that the decision to assist or not is a socially formed process rather than just an individual moral calculation. Its originality is in describing the commonplace meaning-making and adaptive tactics that the public uses to jointly manage ethical ambiguity in shared urban areas, such as contributing without anticipating a material exchange or utilizing politeness as a non-monetary reaction.